Reinforcing State Financial Governance Through an Integrated Approach of Theoretical, Empirical, And Applied Research in Public Sector Accounting - Yudea yudea; Yudaruddin Yanzil Azizil; Sari Dika Karlinda (Polytechnic of State Finance STAN, 2025)
This research investigates the contribution of an integrated approach, encompassing theoretical, empirical, and applied aspects, to the reinforcement of Government Accounting Standards and national financial management in Indonesia. Utilizing a sequential exploratory mixed-methods design, this study examines over one hundred scholarly publications from 2010 to 2025 through a structured literature review, performs panel data regression analysis on 150 regional government entities and ten central agencies (2020-2024), and gathers qualitative insights from 22 strategic informants and three in-depth case studies. Theoretical analysis reveals complex interactions among New Public Management concepts, Institutional Theory, and Accountability Theory, signaling a disconnect between formal Government Accounting Standards application for legitimacy and essential operational execution. Empirically, a positive association is observed between conceptual alignment, the accrual implementation rate (averaging 72 percent), workforce capabilities, and information system optimization with advancements in audit opinions and standard compliance rates. Qualitative findings highlight cultural resistance, deficiencies in competency development programs for recent Statement of Government Accounting Standards (No. 16 and 17), and information technology integration challenges as principal field-level impediments. The amalgamation of these three perspectives substantiates all proposed propositions, affirming that Government Accounting Standards's efficacy depends on a thorough comprehension of these components. This research yields a cohesive conceptual model alongside practical proposals for the Government Accounting Standards Committee and The Institute of Indonesia Chartered Accountants. to refine Government Accounting Standards, thereby advancing national financial administration that is more transparent and accountable.